1984
DOI: 10.1037/h0080846
|View full text |Cite
|
Sign up to set email alerts
|

Human figure drawing in adults: An update of the empirical evidence, 1967–1982.

Abstract: Figure drawing tests continue to be popular with clinicians despite the relatively unfavourable conclusions of a number of published literature reviews. The current paper examines the empirical literature on the reliability and validity of human figure drawing tests, used as a projective device with adult subjects, covering the period between January 1967 and June 1982. The areas surveyed include reliability estimates, evidence relevant to the body-image hypothesis, the validity of hypotheses concerning struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
10

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 131 publications
5
70
0
10
Order By: Relevance
“…Indeed, a number of researchers have suggested specific and non-specific recall benefits of asking children to draw the event in both experimental and applied settings (Burgess & Hartman, 1993;Butler, Gross & Hayne, 1995;Davison & Thomas, 2001;Edwards & Fornham, 1989;Gross & Hayne, 1998Kahill, 1984;Pynoos & Eth, 1986;Thomas & Jolley, 1998;Salmon, 2001;Wesson & Salmon, 2001). As children's spontaneous and self-directed drawings typically portray subject matter and events that are of most interest to them, drawings are likely to stimulate the child to talk about the salient episodes associated with the topic of the drawing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of researchers have suggested specific and non-specific recall benefits of asking children to draw the event in both experimental and applied settings (Burgess & Hartman, 1993;Butler, Gross & Hayne, 1995;Davison & Thomas, 2001;Edwards & Fornham, 1989;Gross & Hayne, 1998Kahill, 1984;Pynoos & Eth, 1986;Thomas & Jolley, 1998;Salmon, 2001;Wesson & Salmon, 2001). As children's spontaneous and self-directed drawings typically portray subject matter and events that are of most interest to them, drawings are likely to stimulate the child to talk about the salient episodes associated with the topic of the drawing.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the global approach involves basing a judgment on all of the features of a drawing. A number of reviewers have concluded that the sign approach typically yields inferences that possess negligible or zero validity (e.g., Kahill, 1984;Klopfer & Taulbee, 1976;Motta, Little, & Tobin, 1993;Thomas & Jolley, 1998). Results have been somewhat better for the global approach.…”
Section: Research On the Assessment Of Psychopathologymentioning
confidence: 99%
“…Nonetheless, with these caveats aside the house-tree-person drawing task continues to be widely used in clinical evaluation projective portfolios for the purpose of developing hypotheses and psychodiagnostic inferences. Incidentally, the house-tree-person drawing test has long been known to be a sensitive test of organic impairment, and along with the Wechsler scales, was among the first instruments to be used for such purposes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In personality research drawings of persons have been used to measure intelligence since the turn of the last century [6][7][8][9]. Thus, a voluminous empirical database on administering, scoring and interpreting standardized drawings already exits.…”
Section: Introductionmentioning
confidence: 99%